THE FACTORS THAT INFLUENCE THE IMPLEMENTATION OF SMOKE FREE CAMPUS POLICY IN UNIVERSITY OF MUHAMMADIYAH YOGYAKARTA - Ema Waliyanti; Yudan Hari Sandika (IJNP (Indonesian Journal of Nursing Practices), 2015)
Smoking is one of the problems in society today that difficult to resolve. There are 6 million deaths each year are caused by smoking. The number of smokers in Indonesia continues to grow, which is dominated by the age of 15 years and above. To overcome these problems the government issued a policy  banning  smoking in the learning process. Universitas Muhammadiyah Yogyakarta (UMY) was one of the places that already have implemented smoke-free campus since 2011, but until now there is smoke in campus. This study was to determine the factors that affect the implementation Kawasan Bersih Bebas Asap Rokok (KBBR) in UMY.This study was a qualitative research with phenomenological approach. The data were taken using the method discussion focus groups, depth interviews and observation. Participants in this study were determined by purposive sampling counted 20 participants consisting of students and campus employees in UMY. The validity of the data in this study was done by using triangulation, triangulation methods and peer debriefing. Data analysis was performed with the help of software open code version 4.2. These results indicate that the factors that affect the implementation KBBR in UMY was knowledge of KBBR, attitudes toward KBBR, lack of socialization and prohibition signs of KBBR, the absence of strict sanctions against violators KBBR and environmental influences. This shows that UMY needs to improve socialization and give strict punishment for violation of KBBR.Keywords: Factors, KBBR, UMY